Implikasi Hukum Ekonomi Syariah terhadap Pengembangan Keuangan Mikro dan Usaha Kecil Menengah - Winario, Mohd; Rinaldi, Rinaldi; Zakir, Muhammad; Lubis, Haniah; Bustanur, Bustanur (EL-EMIR Institute, 2024)
This study aims to analyze the implications of sharia economic law on the development of microfinance and Small and Medium Enterprises (SMEs) in Indonesia. The focus of this study is to identify the application of sharia principles in microfinance, examine the challenges faced by SMEs in accessing sharia financial services, and explore the potential and opportunities of sharia microfinance in supporting SME development. This study uses a qualitative method with a case study approach. Data were collected through in-depth interviews with SMEs, sharia financial practitioners, and sharia financial institutions, and supported by analysis of related literature. The results of the study indicate that the application of sharia economic law in microfinance has a positive impact on SMEs, especially in terms of financial inclusiveness and economic justice. However, there are several challenges that still need to be overcome, such as low sharia financial literacy and limited access to sharia financial institutions, especially in rural areas. The potential of sharia microfinance as a tool for empowering SMEs is very large, but requires adequate regulatory and infrastructure support. This study concludes that with increased literacy, access, and appropriate regulation, sharia microfinance can be a strategic solution to accelerate the growth of SMEs in Indonesia.